THE INFLUENCE OF RICE PRODUCTION, INTERNATIONAL RICE PRICES, POPULATION, AND GROSS DOMESTIC PRODUCT (GDP) ON INDONESIA'S RICE IMPORTS - Sydney Zaneta; Anak Agung Ketut Ayuningsasi (Adisam Publisher, 2025)
Trading activities hold a crucial position in a nation's economy, particularly as a means of fostering diplomatic relations between countries. In the context of strategic commodities such as rice, although production has increased, this growth has not yet fully kept pace with national consumption levels, which are largely driven by the household and industrial sectors. This study aims to examine the impact of rice production, international rice prices, population size, and Gross Domestic Product (GDP) on the volume of rice imports in Indonesia during the period from 1993 to 2023, both in the short and long term. A quantitative approach was employed, utilizing annual time series secondary data over a span of 31 years. Data analysis was conducted using multiple linear regression (OLS) and the Error Correction Model (ECM). The ECM estimation results indicate that all the variables studied tend to move toward a common equilibrium in the long run, suggesting cointegration. The analysis also shows that in the short term, rice production, international rice prices, population, and GDP do not have a significant effect on rice import volumes. However, in the long term, rice production and international rice prices have a positive and significant effect on import volumes, while GDP has a negative and significant effect. On the other hand, population has a positive but statistically insignificant impact on rice imports in Indonesia during the study period. These findings suggest that optimizing domestic rice production and managing international price fluctuations are critical strategies for sustainably controlling rice import volumes. Moreover, stable economic growth significantly contributes to reducing long-term dependency on rice imports.